An Assessment of The Contribution of Community Social Support System in Promoting to the Wellbeing of the Elderly in Hamurwa Sub-County. - Atuheire, Enid (Kabale University, 2024)
The study examined the role of community social support systems in enhancing the well-being of the elderly in Hamurwa Sub County. It aimed to assess how housing support, health support, and nutritional support contribute to the well-being of elderly residents. Conducted across seven parishes in Rubanda District, South Western Uganda, the research employed a case study design, allowing for an in-depth exploration of individuals and groups involved. The target population consisted of elderly individuals aged 60 and above, selected from the seven parishes, and included both men and women. Face-to-face interviews were conducted with key informants from sub-county, parish, and village authorities, guided by an interview protocol, while questionnaires were administered by the researcher. Data analysis involved organizing and interpreting the collected information. Quantitative data from the questionnaires were sorted and edited in the field by research assistants and the researcher, followed by centralized analysis after all responses were collected. The study concluded that adequate housing characterized by habitability, security of tenure, location, and both economic and physical accessibility significantly impacts the well-being of the elderly. Respondents indicated that psychological issues such as depression, isolation, and anxiety negatively affect the well-being of the elderly, suggesting that an increase in these psychological issues correlates with a decline in well-being. Recommendations include ensuring timely payment of retirement benefits to help the elderly meet their social welfare needs. While the government has made progress in improving the pension scheme, the process of accessing pension payments remains complicated and should be streamlined to enhance the well-being of senior citizens. Additionally, adult children and close relatives should take responsibility for the housing needs of their aging parents. In cases where elderly individuals lack relatives, community members should step in to provide housing support. The government could also consider offering housing assistance to the most needy elderly, based on recommendations from local authorities. Institutionalization may be necessary for individuals without land or relatives willing to help. Furthermore, issues related to land tenure should be addressed to prevent land and property grabbing, necessitating coordinated efforts from both the government and NGOs.